2016
DOI: 10.21608/bvmj.2016.31325
|View full text |Cite
|
Sign up to set email alerts
|

Mould contamination of some Egyptian cheese

Abstract: Mould contamination of milk products is a matter of significance in the field of food safety due to its related food spoilage and production of mycotoxins. This study was undertaken to investigate the incidence of mould contamination in different cheese types marketed in Zagazig city, Egypt. Roumy cheese had the highest total mould count followed by cheddar and white cheese types. The prevalent mould genera were Aspergillus, Penicillium, Cladosporium and Alternaria. Further identification of Aspergillus (A) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These results agree with those obtained by Osama et al [47]. El-Badry and Raslan [48] reported that the presence of yeast and molds in cheese samples indicated the occurrence of unsatisfactory conditions during the manufacturing of cheese.…”
Section: Microbiological Quality Of Cheese Samplessupporting
confidence: 92%
“…These results agree with those obtained by Osama et al [47]. El-Badry and Raslan [48] reported that the presence of yeast and molds in cheese samples indicated the occurrence of unsatisfactory conditions during the manufacturing of cheese.…”
Section: Microbiological Quality Of Cheese Samplessupporting
confidence: 92%
“…Moubasher et al (2018b) isolated Aspergillus sp. from Ras cheese, the most common species isolated from surface and core of examined Ras cheese samples were; A. flavus (Zommara and Rashed 2004;ELbagory et al 2014;El-fadaly et al 2015a, b;El-Badry and Raslan 2016;Seddek et al 2016;Elramly et al 2019;Ahmed et al 2020), A. niger (ELbagory et al 2014El-fadaly et al 2015a, b;El-Badry and Raslan 2016;Seddek et al 2016;Younis et al 2016;Elramly et al 2019;Ahmed et al 2020) andA. fumigatus (ELbagory et al 2014;Seddek et al 2016;Younis et al 2016;Elramly et al 2019;Ahmed et al 2020).…”
Section: Aspergillus In Egyptmentioning
confidence: 99%
“…glaucus (El-fadaly et al 2015a, b), A. nidulans (El-fadaly et al 2015a, b;Elramly et al 2019), A. ochraceus (El-fadaly et al 2015aEl-Badry and Raslan 2016;Elramly et al 2019;Ahmed et al 2020), A. oryzae (El-fadaly et al 2015aAhmed et al 2020), A. parasiticus (Zommara and Rashed 2004;El-Badry and Raslan 2016;Younis et al 2016;Ahmed et al 2020), A. sydowii (Ahmed et al 2020), A. terreus (ELbagory et al 2014Embaby et al 2015;Younis et al 2016;Elramly et al 2019) and A. ustus (Seddek et al 2016). Furthermore, Hegazy et al (2014) reported isolation of A.…”
Section: Aspergillus In Egyptmentioning
confidence: 99%
See 1 more Smart Citation